Phorbol-Ester Mediated Suppression of hASH1 Synthesis: Multiple Ways to Keep the Level Down - Benko, Edgar; Winkelmann, Aline; Meier, Jochen C.; Persson, Pontus B.; Scholz, Holger; Fähling, Michael (Frontiers in Molecular Neuroscience, 2011)
hASH1 (human achaete-scute homolog-1), encoded by the human ASCL1 gene, belongs to the family of bHLH (basic helix-loop-helix) transcription factors. hASH1 and its mammalian homologue Mash1 are expressed in the central and peripheral nervous system during development, and promote early neuronal differentiation. Furthermore, hASH1 is involved in the specification of neuronal subtype identities. Misexpression of the transcription factor is correlated with a variety of tumors, including lung cancer and neuroendocrine tumors. To gain insights into the molecular mechanisms of hASH1 regulation, we screened for conditions causing changes in hASH1 gene expression rate. We found that treatment of human neuroblastoma-derived Kelly cells with phorbol 12-myristate 13-acetate (PMA) resulted in a fast, strong and long-lasting suppression of hASH1 synthesis. Reporter gene assays with constructs, in which the luciferase activity was controlled either by the ASCL1 promoter or by the hASH1 mRNA untranslated regions (UTRs), revealed a mainly UTR-dependent mechanism. The hASH1 promoter activity was decreased only after 48 h of PMA administration. Our data indicate that different mechanisms acting consecutively at the transcriptional and post-transcriptional level are responsible for hASH1 suppression after PMA treatment. We provide evidence that short term inhibition of hASH1 synthesis is attributed to hASH1 mRNA destabilization, which seems to depend mainly on protein kinase C (PKC) activity. Under prolonged conditions (48 h), hASH1 suppression is mediated by decreased promoter activity and inhibition of mRNA translation.